"All Your Ages at the Mercy of My Loves": Rewriting History in John Berryman's Homage to Mistress Bradstreet. (November 2014) - JORDAN, AMY
<x content-type="archive" xml:space="preserve">Abstract</x> Since its 1953 publication, John Berryman's Homage to Mistress Bradstreet has incited debate. The text's dialogue with the first published poet of colonial North America has been described as a factual study, a redaction of adultery and a veiled critique of modern society. It is seldom noted, however, that Berryman's strategy of "modulat[ing]" his voice into Anne Bradstreet's raises key questions regarding his reappropriation of her life and writing. Does Homage's conscious ventriloquism problematize its status as a "historical" poem? And how might this revised understanding illuminate the work's relation to America's origins? This paper proposes a more multifaceted context for Homage's composition than has hitherto been recognized. Through mapping the poem's rewriting of history, I demonstrate it to be the product of both national and literary anxieties: if voicing Bradstreet enables Berryman to interrogate the American Dream's legacy, her canonical status casts scrutiny upon the contemporary poet's role in an age of sociopolitical tensions. Foregrounding Berryman's public self-positioning in Homage invites a reassessment of his engagements with society that liberates his oeuvre from "confessional" designations. As a result, it opens the way for readings that might situate Homage and The Dream Songs within the wider tradition of American epic poetry.